Dopaminergic Inhibition of Na+ Currents in Vestibular Inner Ear Afferents - Meredith, Frances L.; Rennie, Katherine J. (Frontiers in Neuroscience, 2021)
Inner ear hair cells form synapses with afferent terminals and afferent neurons carry signals as action potentials to the central nervous system. Efferent neurons have their origins in the brainstem and some make synaptic contact with afferent dendrites beneath hair cells. Several neurotransmitters have been identified that may be released from efferent terminals to modulate afferent activity. Dopamine is a candidate efferent neurotransmitter in both the vestibular and auditory systems. Within the cochlea, activation of dopamine receptors may reduce excitotoxicity at the inner hair cell synapse via a direct effect of dopamine on afferent terminals. Here we investigated the effect of dopamine on sodium currents in acutely dissociated vestibular afferent calyces to determine if dopaminergic signaling could also modulate vestibular responses. Calyx terminals were isolated along with their accompanying type I hair cells from the cristae of gerbils (P15-33) and whole cell patch clamp recordings performed. Large transient sodium currents were present in all isolated calyces; compared to data from crista slices; resurgent Na+ currents were rare. Perfusion of dopamine (100 µM) in the extracellular solution significantly reduced peak transient Na+ currents by approximately 20% of control. A decrease in Na+ current amplitude was also seen with extracellular application of the D2 dopamine receptor agonist quinpirole, whereas the D2 receptor antagonist eticlopride largely abolished the response to dopamine. Inclusion of the phosphatase inhibitor okadaic acid in the patch electrode solution occluded the response to dopamine. The reduction in calyx sodium current in response to dopamine suggests efferent signaling through D2 dopaminergic receptors may occur via common mechanisms to decrease excitability in inner ear afferents.